Podmioty ekonomii społecznej i przedsiębiorstwa prywatne. Bariery współpracy = Social economy entities and private enterprises. Barriers to cooperation - Mielczarek-Żejmo, Anna; Sikora, Rafał (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The study analyses cross-sector cooperation in social economy. This cooperation is perceived as an important factor in the development of social economy, which is one of the mechanisms of social change and an answer to challenges related to social exclusion and disintegration. This paper raises questions about the types of barriers to cooperation between social economy entities and business sector entities based on a literature review. The answers are provided by the literature review. The authors find that there are three types of barriers to cross-sector cooperation between business and social economy. These are institutional, mental and operational barriers.
Keywords: ekonomia społeczna; sektor rynku; współpraca międzysektorowa; social economy; market sector; cross-sector cooperation